Verbal and non-verbal skills in early childhood: dimensionality, developmental trajectories, and gender differences - Elnes, Magdalena; Hansen, Joakim Evensen; Lervåg, Arne; Hatlevik, Ove Edvard; Reikerås, Elin Kirsti Lie (Frontiers in Psychology, 2024)
This study examines the validity of two subscales from the British Ability Scales -Third Edition, measuring verbal (expressive vocabulary) and non-verbal (reasoning) cognitive skills for toddlers (age three) and preschoolers (age five), in a Norwegian context across genders.Descriptive statistics revealed item selection criteria that included specific items within each subscale. Subsequently, Confirmatory Factor Analysis established the subscales' dimensionality (Naming Vocabulary and Picture Similarities; N = 1094) and confirmed measurement invariance across genders. Overall, the results provided support for the validity of the revised assessments within the Norwegian context. Further, we investigated the relationship between verbal and non-verbal factors using correlation analysis and Structural Equation Modeling. The findings revealed that the verbal factor at age three strongly predicted the verbal factor at age five and significantly influenced the non-verbal factor at age five. The non-verbal factor at age three exhibited a moderate predictive relationship with the non-verbal factor at age five. However, it did not significantly predict the verbal factor at age five. In terms of gender differences, girls had higher scores on the verbal factor at age three, and showed a stronger correlation between the nonverbal factor at age three and the verbal factor at age five. In summary, this research provides valuable insights into cognitive skill measurement and development in a Norwegian context and highlights possible variations across gender. The study's findings, limitations, and implications are discussed.